Functional 3D Neural Mini‐Tissues from Printed Gel‐Based Bioink and Human Neural Stem Cells. Issue 12 (29th March 2016) - Gu, Qi; Tomaskovic‐Crook, Eva; Lozano, Rodrigo; Chen, Yu; Kapsa, Robert M.; Zhou, Qi; Wallace, Gordon G.; Crook, Jeremy M.
Abstract : Direct‐write printing of stem cells within biomaterials presents an opportunity to engineer tissue for in vitro modeling and regenerative medicine. Here, a first example of constructing neural tissue by printing human neural stem cells that are differentiated in situ to functional neurons and supporting neuroglia is reported. The supporting biomaterial incorporates a novel clinically relevant polysaccharide‐based bioink comprising alginate, carboxymethyl‐chitosan, and agarose. The printed bioink rapidly gels by stable cross‐linking to form a porous 3D scaffold encapsulating stem cells for in situ expansion and differentiation. Differentiated neurons form synaptic contacts, establish networks, are spontaneously active, show a bicuculline‐induced increased calcium response, and are predominantly gamma‐aminobutyric acid expressing. The 3D tissues will facilitate investigation of human neural development, function, and disease, and may be adaptable for engineering other 3D tissues from different stem cell types. Abstract : Three dimensional (3D) human neural tissue is generated by bioprinting human neural stem cells with a novel polysaccharide‐based bioink . After bioink gelation, encapsulated stem cells self‐renew and differentiate to neuronal and neuroglial cell lineage. Neurons are predominantly gamma‐aminobutyric acid expressing, establish networks, are spontaneously active, and show a bicuculline‐induced increased calcium response.